2022
DOI: 10.1155/2022/2693080
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Age and Gender Differences in ICT Cybersecurity Behaviour

Abstract: Known age differences exist in relation to information and communication technology (ICT) use, attitudes, access, and literacy. Less is known about age differences in relation to cybersecurity risks and associated cybersecurity behaviours. Using an online survey, this study analyses data from 579 participants to investigate age differences across four key cybersecurity behaviours: device securement, password generation, proactive checking, and software updating. Significant age differences were found; however,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 53 publications
4
11
0
Order By: Relevance
“…In the first part of the results section, we report the bivariate correlations and focus on the relationship between use of digital media, security precautions, and technology commitment, flexible goal adjustment, and age. 1) replicate the finding from an earlier study [10] in which age was a positive predictor of security precautions (password generation, proactive checking, and updating). They show the expected negative association between the use of social networks and age, but emailing/surfing was positively associated with age.…”
Section: Resultssupporting
confidence: 78%
See 3 more Smart Citations
“…In the first part of the results section, we report the bivariate correlations and focus on the relationship between use of digital media, security precautions, and technology commitment, flexible goal adjustment, and age. 1) replicate the finding from an earlier study [10] in which age was a positive predictor of security precautions (password generation, proactive checking, and updating). They show the expected negative association between the use of social networks and age, but emailing/surfing was positively associated with age.…”
Section: Resultssupporting
confidence: 78%
“…Few studies focused on age differences. Positive age correlations were found for all domains except for device securement [10], but the effects were only small or modest. A study on online privacy perception showed that older adults reported a significantly higher awareness of privacy than younger users and protected their data more actively [16].…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…Researchers have focused on how personality characteristics, such as the tendency to be impulsive, may be associated with more risky online behaviors and therefore present an opening to attacks (Hadlington, 2017). Other work focused on age and gender has examined whether individuals engage in certain secure practices and found that older individuals were less likely than others to secure their devices but more likely to generate secure passwords and update their devices and no differences by gender (Branley-Bell et al , 2022). While the findings are important, as they highlight the utility of understanding public cyber behavior, they do not offer insight into the extent to which public users are objectively aware or knowledgeable about secure cyber techniques nor does it explore other demographics such as education and income.…”
Section: Information Security and General User Knowledgementioning
confidence: 99%